2015
DOI: 10.1111/all.12674
|View full text |Cite
|
Sign up to set email alerts
|

Allergic sensitization is associated with inadequate antioxidant responses in mice and men

Abstract: Our study indicates that oxidative stress condition before allergen exposure due to an inadequate antioxidant response may prime for allergic Th2 responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…Sensitization to house dust mite (HDM) in mice was associated with an incapacity to upregulate Nrf2 and HO-1 upon induction of oxidative stress by mite proteases. In BALB/c mice, exposure to a HDM extract with trace levels of endotoxins (LT-HDM) was not sufficient to induce a Th2 immune response [32]. This is in accordance with several studies showing that TLR4 triggering by LPS is crucial for the initiation of allergen-specific Th2 responses IN BALB/c mice [74,75].…”
Section: Allergic Sensitization Is Associated With a Decreased Antsupporting
confidence: 67%
See 4 more Smart Citations
“…Sensitization to house dust mite (HDM) in mice was associated with an incapacity to upregulate Nrf2 and HO-1 upon induction of oxidative stress by mite proteases. In BALB/c mice, exposure to a HDM extract with trace levels of endotoxins (LT-HDM) was not sufficient to induce a Th2 immune response [32]. This is in accordance with several studies showing that TLR4 triggering by LPS is crucial for the initiation of allergen-specific Th2 responses IN BALB/c mice [74,75].…”
Section: Allergic Sensitization Is Associated With a Decreased Antsupporting
confidence: 67%
“…In our lab, we recently demonstrated that HDM proteases are responsible for the capacity of HDM allergens to induce oxidative stress. Partial inhibition of protease activity dramatically decreased the capacity of HDM to induce oxidative stress and the subsequent allergic inflammation in mice [32]. …”
Section: Protease Allergens Trigger Reactive Oxygen Species Producmentioning
confidence: 99%
See 3 more Smart Citations